Nilai-nilai Pendidikan pada Ayat-ayat Amtsal dalam Al-Quran Surah Al-baqarah - Bakar, Abu (SYAMIL: Jurnal Pendidikan Agama Islam (Journal of Islamic Education), 2017)
The background of this research is because of the curiosity about the moral value of amtsal verse that sometimes Allah gives a parable to the certain class, and with that parable it can attract the reader attention, and it even can arouse the heart of the reader to make them to think back. And make an equalof their self and the class that Allah parable in that verse. Moreover about the researcher’s conviction about the act of Qur’an in education, start from lesson of the education values that really noble and exalted, until the very latest technology invention of scientists from medieval until modern. That’s all not in spite of the muslim’s holy book contents, its Al-Qur’an Al-Karim. And the object of this research are very Qur’an verse in al-Baqarah. The second division is madinah and it’s the longest division in Qur’an, and the number is 286 verse. And its also called as Qur’an fustat, because it’s also have some laws that didn’t metion in other devision. The devision that also contains lats of superiority for people that apply it. That’s for not too big and to much criticism to that verse definition. The research had classification to deternine the verse with criteria that exist in tasybih tradition for the explanation in tekstual if that verse is amtsal verse. And that verse is al-Baqarah, 17-19, verse 146, verse 171, and verse 265. After analyze that verse by the comentator’s explanations. There are some education’s value that we can learn from the amtsal verse in this research. That value must be glutinous in muslim’s self to make them can reach the predicate as an Allah’s slave in Allah’s side. That values are faith, obidiens value, moral valuegod’sguidencs value, religious proselytizing motivasi value, unity of god value, sincere value, thanks value, benefit value, conviction value, work’s etous value, expliat value, and tolerant value.